ANALISIS KEMAMPUAN GURU DALAM MENERAPKAN PENDEKATAN SAINTIFIK PADA PEMBELAJARAN SOSIOLOGI KELAS XI IPS MAS AL-MUSTAQIM - yarso, Jumiati; Salim, Izhar; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is titled Analysis of Teacher's Ability in Applying a Scientific Approach to Learning Sociology in Class XI IPS MAS AL-Mustaqim. The formulation of the problem is as follows (1) What is the teacher's ability to apply the scientific approach to learning sociology in class XI IPS MAS AL-Mustaqim?.(2) What are the teacher's obstacles in applying the scientific approach to learning sociology in class XI IPS MAS AL-Mustaqim?.The research method used is qualitative descriptive research. The research subjects were sociology teachers who taught in class XI IPS and students of class XI IPS.Data collection techniques used were observation, interviews and documentation.The results of the study show the following findings:(1) the teacher's ability to apply the scientific approach is good, it can be seen from the teacher applying the five-step scientific approach in accordance with Minister of Education and Culture Number 81a of 2013 concerning Implementation of the Curriculum.(2) barriers experienced by teachers in applying the scientific approach, namely students are less focused and less active in learning activities, teachers are hampered in allocating time during the learning process,and teachers are hampered by the lack of facilities provided by the school.Â Keywords: Teacher, Scientific Approach, Sociology Learning